Testing the evidence integration triangle for implementation of interventions to manage behavioral and psychological symptoms associated with dementia: Protocol for a pragmatic trial. Issue 3 (27th February 2018) - Resnick, Barbara; Kolanowski, Ann; Van Haitsma, Kimberly; Galik, Elizabeth; Boltz, Marie; Ellis, Jeanette; Behrens, Liza; Flanagan, Nina M.; Eshraghi, Karen J.; Zhu, Shijun
ABSTRACT: Behavioral and psychological symptoms of dementia (BPSD) include aggression, agitation, resistiveness to care, depression, anxiety, apathy, and hallucinations. BPSD are common in nursing home residents and can be ameliorated using person‐centered approaches. Despite regulatory requirements, less than 2% of nursing homes consistently implement person‐centered behavioral approaches. In a National Institute of Nursing Research‐funded research protocol, we are implementing a pragmatic cluster randomized clinical trial designed to enable staff in nursing homes to reduce BPSD using behavioral approaches while optimizing function, preventing adverse events, and improving quality of life of residents. The implementation is based on use of the Evidence Integration Triangle (EIT), a parsimonious, community‐engaged participatory framework that is well suited to the complexity and variability in the nursing home environment. A total of 50 nursing home communities will be randomized to EIT‐4‐BPSD or education only. Primary Aim 1 is to determine if communities exposed to EIT‐4‐BPSD demonstrate evidence of implementation evaluated by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE‐AIM) criteria. Primary Aim 2 is to evaluate the feasibility, utility, and cost of the EIT approach in EIT‐4‐BPSD communities.